Socio-Economic Factors Assessment Affecting the Adoption of Soil Conservation Technologies on Rwenzori Mountain - Nabalegwa Wambede Muhamud (Faculty of Geography, Universitas Gadjah Mada, 2015)
This study analysed the role of socio-economic factors in influencing farmers’ adoption to soil conservation technologies in Bugoye Sub-county, Rwenzori Mountain. A cross sectional household survey design was used in this study, using systematic sampling to obtain 150 household samples. Qualitative analysis and chi-square tests were used to analyze these data. Results indicated that only 54% of the sampled households have adopted soil conservation, and revealed that eight of the nine factors significantly influenced farmers’ adoption, which are slope, farm size, farm distance from home, education level, family income, training, membership to NGOs, and credit accessibility. Only family size was insignificant. Other constraints are labour demands, cost of conservation work, land fragmentation, crop pests, and the limited agricultural extension services. It is recommended to perform training for farmers on designing soil conservation structures. Policies for empowering farmers with extra income are crucial to increase the adoption of soil conservation efforts.